Promoting Community Pharmacy Practice for Chronic Obstructive Pulmonary Disease (COPD) Management: A Systematic Review and Logic Model - Hu Y; Yao D; Ung COL; Hu H (International Journal of COPD, 2020)
Yuqi Hu, Dongning Yao, Carolina Oi Lam Ung, Hao Hu State Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, People’s Republic of ChinaCorrespondence: Carolina Oi Lam Ung; Hao HuState Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, N22-2057, Taipa, Macau. People’s Republic of ChinaTel +853 88228538Email carolinaung@um.edu.mo; haohu@um.edu.moPurpose: This study aimed 1) to identify and analyse the professional services provided by community pharmacists for chronic obstructive pulmonary disease (COPD) management; and 2) to develop a logic model for community pharmacy practice for COPD management.Methods: A systematic review with a logic model was applied. English-language databases (PubMed, Web of Science, Embase, and Scopus) and a Chinese database (CNKI) were searched for articles published between January 2009 and June 2019. Studies concerning pharmacists and COPD were identified to screen for studies that focused on professional services provided at a community pharmacy level. Evidence on economic, clinical, and humanistic outcomes of interventions was summarized.Results: Twenty-five articles were included in this study. Four categories of COPD-related interventions by community pharmacists were identified: 1) primary prevention; 2) early detection; 3) therapy management; and 4) long-term health management. The most common outputs examined were improvement in inhaler technique, medication adherence, and rate of smoking cessation. The clinical (improved quality of life, reduced frequency and severity of symptoms and exacerbation), humanistic (patient satisfaction), and economic (overall healthcare costs) outcomes were tested for some interventions through clinical studies. Contextual factors concerning pharmacists, healthcare providers, patients, facilities, clinic context, and socio-economic aspects were also identified.Conclusion: Studies in the literature have proposed and examined different components of professional services provided by community pharmacists for COPD management. However, relationships among outcomes, comprehensive professional services of community pharmacists, and contextual factors have not been systematically tested. More well-designed, rigorous studies with more sensitive and specific outcomes measures need to be conducted to assess the effect of community pharmacy practice for COPD management.Keywords: community pharmacy, community pharmacist, chronic obstructive pulmonary disease, COPD, systematic review, logic model